The Effect of Using Means –Ends Analysis (MEA) Model on Students’ Raeding Comprehesion of Recount Tetx (at the Eighth grade of SMP Swasta Keluarga Siambaton Napa Manduamas in Academic Year 2020/2021) - indah sari indahsarimungkur (JURNAL LINER (Language Intelligence and Educational Research), 2021)
The purpose of this research are to found out: 1) The application of means –ends analysis model on students’ reading comprehension of recount text, 2) The students’ reading comprehension of recount text ability before and after using means –ends analysis model, 3) whether there is any significant effect of means –ends analysis model on students’ reading comprehension of recount text ability at the Eighth Grade of SMP Swasta Keluarga Siambaton Napa Manduamas.This research uses experimental method with the pre-experimental design by using one-group pretest and posttest design. The population of this research is all the VIII Grade students’of SMP Swasta Keluarga Siambaton Napa Manduamas which consist of 70 students and the samples were 20 students gotten by using porposive sampling. In collecting the data, the researcher used observation sheet. Instrument of the research was observation and test was composition test. The result of the research are 1) application of means –ends analysis model was 3.8, it was categorized “very good”. 2) The mean score of the students’ before using means –ends analysis model was 35, it was categorized “bad”. Meanwhile after using mens –ends analysis model was 85, it was categorized “good”. 3) The result of analysis showed that ttest is bigger than ttable (ttest10.2> ttable 2.05). So, the hypothesis was accepted. It means that there is any significant effect of means –ends analysis model on students’ raeding comprehension of recount text ability at the VIII Grade of SMP Swasta Keluarga Siambaton Napa Manduamas.